Introduction of the military prosecutor’s office as an element of military justice - Кальчук, Олексій Миколайович (Теоретичні питання юриспруденції і проблеми правозастосування: виклики ХХІ століття : тези доп. учасників X Міжнар. наук.-практ. конф. (Харків, 25 трав. 2025 р.), 2025)
The article is devoted to the possibility of introducing the military prosecutor’s office as an element of military justice. It is proved that the functioning of the Specialized Military Prosecutor’s Office, which is staffed by military personnel, under the conditions of the introduction of the legal regime of martial law and a special period in Ukraine, an effective solution to the tasks of protecting national interests from military threats will be ensured, maintaining proper law and order in the military sphere, including supervising the observance by the intelligence agencies of Ukraine of the laws of Ukraine and the observance of legality by the military counterintelligence bodies of the Security Service of Ukraine, carrying out counterintelligence activities, ensuring the protection of the rights and legitimate interests of military personnel and their families, as well as improving the efficiency of detection, documentation and investigation of war crimes, crimes of genocide and crimes against humanity committed by the Russian Federation on the territory of Ukraine, as well as effective supervision of the system of vowel and secret search and counterintelligence measures, carried out with the use of operational and operational-technical means (Articles 2 and 5 of the Law of Ukraine «On operational-search activities»). The specialized military prosecutor’s office has been proposed to defi ne as a legal entity of public law, which has separate property that is state property, accounts in bodies that carry out treasury services for budget funds, a seal depicting the State Emblem of Ukraine and its name.